UJI TOKSISITAS AKUT EKSTRAK ETANOL DAUN BUAS-BUAS (Premna serratifolia Linn.) TERHADAP LARVA UDANG (Artemia salina Leach) DENGAN METODE BRINE SHRIMPLETHALITY TEST (BSLT) - Parawansah, Parawansah; Nuralifah, Nuralifah; Akib, Nurlliyin; Antrie, Geong (Prosiding Seminar Nasional Riset Kuantitatif Terapan 2017, 2017)
Buas-buas (Premna serratifolia Linn.) belongs to the family Verbenaceae has been used as a traditional medicine. The aims of this research are to determine the compound, extract characteristics and potential toxicity (LC50) of ethanol extract of buas-buas leaves. The used method is Brine Shrimp Lethality Test (BSLT). The test consisted of six concentration treatments namely 1000, 750, 500, 250, 100 ppm and negative control with three replications. In each concentration used 10 Artemia salina leach larvae, and observations were made during 24 hours of larvae mortality. The content of phytochemical compounds from the buas-buas leaves are alkaloids, flavonoids, saponins and tannins. Characterization extract showed 62,21% contents of ethanol soluble extract, 41,5% contents of water soluble extract, 14,1% contents moisture and 4,1% contents ash. LC50 value was determined by probit analysis. The result of LC50 is 133,96 ppm. LC50<1000 ppm showed that the ethanol extract of buas-buas leaves as toxic.Kata kunci— Premna serratifolia Linn., Brine Shrimp Lethality Test (BSLT), LC50, Artemia salina Leach